Biogeographic differences in plant–soil biota relationships contribute to the exotic range expansion of Verbascum thapsus. Issue 23 (28th October 2020) - Dieskau, Julia; Bruelheide, Helge; Gutknecht, Jessica; Erfmeier, Alexandra
Abstract: Exotic plant species can evolve adaptations to environmental conditions in the exotic range. Furthermore, soil biota can foster exotic spread in the absence of negative soil pathogen–plant interactions or because of increased positive soil biota–plant feedbacks in the exotic range. Little is known, however, about the evolutionary dimension of plant–soil biota interactions when comparing native and introduced ranges. To assess the role of soil microbes for rapid evolution in plant invasion, we subjected Verbascum thapsus, a species native to Europe, to a reciprocal transplant experiment with soil and seed material originating from Germany (native) and New Zealand (exotic). Soil samples were treated with biocides to distinguish between effects of soil fungi and bacteria. Seedlings from each of five native and exotic populations were transplanted into soil biota communities originating from all populations and subjected to treatments of soil biota reduction: application of (a) fungicide, (b) biocide, (c) a combination of the two, and (d) control. For most of the investigated traits, native populations showed higher performance than exotic populations; there was no effect of soil biota origin. However, plants developed longer leaves and larger rosettes when treated with their respective home soil communities, indicating that native and exotic plant populations differed in their interaction with soil biota origin. The absence of fungi and bacteria resulted in a higher specific root length, suggesting that V. thapsus may compensate the absence of mutualistic microbes by increasing its root–soil surface contact. Synthesis. Introduced plants can evolve adaptations to soil biota in their new distribution range. This demonstrates the importance of biogeographic differences in plant–soil biota relationships and suggests that future studies addressing evolutionary divergence should account for differential effects of soil biota from the home and exotic range on native and exotic populations of successful plant invaders. Abstract : We tested for differential effects of soil microbes from the native and introduced ranges for the exotic range expansion of Verbascum thapsus in a reciprocal transplant experiment. We found significant interactions between plant range origin and soil biota origin and suggest that V. thapsus may compensate a lack of mutualistic microbes by increasing root surface. Our results emphasize that the evolutionary dimension of plant–soil biota interactions needs to be considered in explaining plant invasions.